2021
DOI: 10.21831/jc.v18i1.39377
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Ksatria Bela Negara comic through the Webtoon for the prevention and control Covid-19

Abstract: During the Covid-19 pandemic, everyone must be at home and keep a distance using a mask. The spread massively. It becomes the basis for all stakeholders to find solutions, both in the form of preventive (prevention) and curative (cure). One of the strategic educational media used to prevent and overcome covid-19 for the current generation of digital natives is through digital comics or webtoons. Comics in digital form has many advantages over printed comics. Based on this, the research aims to find out how the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 13 publications
(16 reference statements)
0
2
0
3
Order By: Relevance
“…Furthermore, in this study, the experimental group had a statistically significantly higher PSMK-PL than the control group immediately after participation in the educational program and after 2 weeks. In previous studies, narrative-based educational information from comic books had an effect on pregnant women's knowledge of health risks related to climate change [44] and on knowledge about the prevention and management of COVID-19 [42]. Cartoons were found to be valuable as a health information medium [18] and had an effect on students' academic achievement in social studies [21].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, in this study, the experimental group had a statistically significantly higher PSMK-PL than the control group immediately after participation in the educational program and after 2 weeks. In previous studies, narrative-based educational information from comic books had an effect on pregnant women's knowledge of health risks related to climate change [44] and on knowledge about the prevention and management of COVID-19 [42]. Cartoons were found to be valuable as a health information medium [18] and had an effect on students' academic achievement in social studies [21].…”
Section: Discussionmentioning
confidence: 94%
“…Unlike the passive nature of these formats, webtoons allow posting opinions and "likes" which encourage bidirectional engagement, while presenting stories that readers can relate to. A recent study used a webtoon to provide education on COVID-19 infection prevention and reported that webtoon education had an educational effect on knowledge development and positive attitude formation through emotions and inducing preventive behavior [42]. Meanwhile, another study reported that women of childbearing age wished for individually tailored prepregnancy health information, preferred sources of prepregnancy health information, and preferred learning through the experiences of other women when planning pregnancy [14].…”
Section: Discussionmentioning
confidence: 99%
“…Budaya politik merupakan pola perilaku suatu masyarakat dalam kehidupan bernegara, penyelenggaraan administrasi negara, politik pemerintahan, hukum, adat istiadat, dan norma kebiasaan yang dihayati oleh seluruh anggota masyarakat yang mempunya sikap bela negara setiap harinya https://journal.actual-insight.com/index.php/decive DOI : (Anggraeni et al, 2021). Budaya politik juga dapat di artikan sebagai suatu sistem nilai bersama suatu masyarakat yang memiliki kesadaran untuk berpartisipasi dalam pengambilan keputusan kolektif dan penentuan kebijakan publik untuk masyarakat seluruhnya.…”
Section: Pendahuluanunclassified
“…Oleh karena itu, sudah semestinya pemerintah mengeluarkan sebuah solusi yang mampu meningkatkan kembali partisipasi politik warga negaranya. Mengingat, bahwa partisipasi politik ini sangat dibutuhkan bagi kelangsungan hidup negara (Anggraeni et al, 2021) Adapun di era perkembangan teknologi komunikasi dan informasi yang terjadi sekarang ini, pemanfaatan media massa bisa dijadikan sebagai solusi alternatif untuk menangani permasalahan partisipasi politik di Indonesia (Febriyana, 2022). Dikatakan demikian, karena disamping adanya hubungan yang tak terpisahkan antara media dan politik, media massa juga mempunyai salah satu fungsi dan tujuan untuk pembentukkan karakter mengenai beberapa hal, baik dalam kehidupan seharihari seperti sosial, ekonomi, budaya, dan khususnya politik (Cahyono, 2016).…”
Section: Pendahuluanunclassified